Development of organic porous material from pineapple waste as a support for enzyme and dye adsorption - Veeramalai, Sangeetha; Nurfadhila Nasya, Ramlee; Hilman Ibnu, Mahdi; Nor Hasmaliana, Abdul Manas; Aizi Nor Mazila, Ramli; Rosli, Md Illias; Nur Izyan, Wan Azelee (Elsevier B.V., 2022)
The transformation of agricultural wastes such as pineapple waste into valuable product such as biochar will be of great advantage. Biochar is a black carbon produced by pyrolysis which can act as good adsorbent for organic substances due to the high porosity characteristic. Due to the instability and the non-recyclability factor of free enzymes, the use of immobilized enzyme is getting more attraction. Furthermore, biochar or activated carbon (AC) has been widely used in industries to adsorb pollution such as dye. In this study, process pyrolysis was used to convert pineapple waste biomass (PWB) into useful adsorbent such as biochar (BC) and activated carbon (AC) for lipase immobilization and RBBR dye adsorption. Several steps such as impregnation of PWbB with nitric acid, and process pyrolysis of pineapple waste at various temperatures and residence time have been performed. Studies of characterization of biochar such as Thermogravimetric analysis (TGA), Brunauer – Emmett – Teller (BET), Fourier Transform Infra-Red (FTIR) and Scanning Electron Microscopy (SEM) were accomplished to analyze the differences in performance. The performance of BC in lipase immobilization and RBBR dye adsorption were investigated by varying parameters i.e. initial concentration, physical size of PWB (grounded and non-grounded pineapple waste (PW) biomas) and physical size of BC (crushed and non-crushed BC). The achievements of generated BC were compared with commercial AC. The result shows the highest amount of protein adsorbed during immobilization was achieved at F500 1 h PWbB (92.99%). Meanwhile, the maximum dye removal was achieved at F 600.5 h PWbB (83.59%). Adsorption kinetics studies insinuate that the overall process follows the pseudo-first-order where the process was influenced by intraparticle and film diffusion while equilibrium isotherm studies is best described by Langmuir isotherm models. As a conclusion, the conventional liability burden of pineapple waste is possible to be transformed into valuable commodity especially for waste treatment.